1983
DOI: 10.1227/00006123-198308000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Hydrocephalus in Cerebral Cysticercosis: Implications for Therapy

Abstract: Patients with hydrocephalus secondary to cerebral cysticercosis are a highly heterogeneous group. The mechanisms of hydrocephalus in these patients are multiple. Intraventricular cysts may be found in the 3rd and 4th ventricles, the sylvian aqueduct, and the foramen of Monro. Intraventricular cysts can be suspected when the 3rd and 4th ventricles or aqueduct remain enlarged despite shunting. Intraventricular contrast medium demonstrates the presence of the parasites. The intraventricular cysts should be remove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(32 citation statements)
references
References 0 publications
0
29
0
3
Order By: Relevance
“…Because the foramina of Luschka and Magendie may also be occluded by the thickened leptomeninges and parasitic membranes, noncommunicating hydrocephalus subsequently may develop. 29 Small penetrating arteries arising from the circle of Willis are frequently affected by the subarachnoid inflammatory reaction elicited by meningeal cysticerci, and this may cause occlusion of the lumen of the vessel and the subsequent development of cerebral infarctions. 13,43 Ventricular cysticerci also cause an inflammatory reaction if they are attached to the choroid plexus or the ventricular wall.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because the foramina of Luschka and Magendie may also be occluded by the thickened leptomeninges and parasitic membranes, noncommunicating hydrocephalus subsequently may develop. 29 Small penetrating arteries arising from the circle of Willis are frequently affected by the subarachnoid inflammatory reaction elicited by meningeal cysticerci, and this may cause occlusion of the lumen of the vessel and the subsequent development of cerebral infarctions. 13,43 Ventricular cysticerci also cause an inflammatory reaction if they are attached to the choroid plexus or the ventricular wall.…”
mentioning
confidence: 99%
“…Hydrocephalus, related to cysticercal arachnoiditis, granular ependymitis, or ventricular cysts, is the most common cause of this syndrome. 29 Increased intracranial pressure also occurs in patients with giant cysts and in those with cysticercal encephalitis. The latter manifestation is a severe form of the disease, more common in children and young women, that occurs as the result of a massive cysticercal infection of the brain parenchyma inducing an intense immune response and diffuse brain edema.…”
mentioning
confidence: 99%
“…8 It may occur because of several different mechanisms that obstruct CSF pathways: intraventricular cysts, ependymitis, residual arachnoidal fibrosis, or compression by a neighboring intraparenchymal cyst. 9,21 In some cases, hydrocephalus is well controlled with CSF shunting, whereas in others there are disease exacerbations, shunt blockage, and elevated mortality, [8][9][10][11] even when cysts are not detectable on CT. 22 We explored the presence of circulating parasite antigen in patients with "resolved" cysticercosis to assess the presence of live parasites in patients with hydrocephalus compared with patients with parenchymal calcifications only. The study demonstrated that a significant proportion (approximately half) of hydrocephalus patients present with high levels of circulating parasite antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Intraventricular neurocysticercal cysts occur singly or in multiples and frequently coexist with parenchymal and sub-arachnoid cysts (10;21-23). Intracranial hypertension is a common manifestation of extraparenhymal NCC and the increased intracranial pressure can be from the mass effect of a giant subarachnoid cyst (27), or from obstructive hydrocephalus produced by direct obstruction of the ventricular system by a cyst (28), distortion of ventricular CSF pathways (29), or blockage of CSF pathways within the subarachnoid space from the inflammatory reaction (28). However, a cyst in the fourth ventricle tends to be solitary, without accompanying parenchymal cysts (10;21-23).…”
Section: Intraventricular Nccmentioning
confidence: 99%